Genetics of immune-mediated disorders: from genome-wide association to molecular mechanism - Kumar, Vinod (Curr Opin Immunol, 2014)
Genetic association studies have identified not only hundreds of susceptibility loci to immune-mediated diseases but also pinpointed causal amino-acid variants of HLA genes that contribute to many autoimmune reactions. Majority of non-HLA genetic variants are located within non-coding regulatory region. Expression QTL studies have shown that these variants affect disease mainly by regulating gene expression. We discuss recent findings on shared genetic loci between infectious and immune-mediated diseases and provide potential clues to explore genetic associations in the context of these infectious agents. We propose that the interdisciplinary studies (genetics-genomics-immunology-infection-bioinformatics) are the future post-GWAS approaches to advance our understanding of the pathogenesis of immune-mediated diseases.